The dictionary of physical geography - Thomas, David S. G. (John Wiley & Sons, Ltd., 2016)
"This fully-revised comprehensive fourth edition covers the whole field of physical geography including climate and atmosphere, geomorphology, biogeography, hydrology, oceans, Quaternary, environmental change, soils, remote sensing and GIS. This new edition reflects developments in the discipline during the last decade, with the expert advisory group providing an international perspective on the discipline of physical geography."